EFL Learner’s Literary Competence Mapping through Reader-Response Writing Assessed using CCEA GCSE Mark Scheme - Suprayogi, Suprayogi; Samanik, Samanik; Novanti, Elza Aqilla; Ardesis, Yoana (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Abstract: In literary education, literary competence lies in important position as it reflects students’ critical thinking ability to understand text as a whole and connect it to both their experience and social phenomenon. Recently, the research on literary competence focuses on the implementation of reader-response writing; however, it rarely highlights the importance of literary competence mapping through the quantification of the responses. This research aims at revealing the implementation of students’ literary competence mapping by using reader-response writing and The Council for the Curriculum Examinations and Assessment (CCEA) General Certificate of Secondary Education (GCSE) Mark Scheme for literature subject for the assessment. Seven reader response strategies by Beach and Marshal (1991) were used as the framework. Selecting 21 students of English Literature in Prose Analysis class as the research object, this research employed qualitative descriptive method. The result shows, in completing seven reader responses, students provide various answers reflecting their ability to get into the stories. The students mostly find it difficult to describe setting of place and time and their influence to the plot of the story. In assessment process, several adjustments on distributing points of CCEA GCSE Mark Scheme for literature subject.  Mark Scheme in each strategy have been made. Almost half of the students are in the band 4 and band 5 meanwhile the rest of them are in band 2 and band 3. This research concludes that reader-response writing and CCEA GCSE Mark Scheme can be alternative to map the students’ literary competence. The research further suggest that the students should be exposed more on the analysis of setting and on the argumentation building on how they should provide sufficient reason and textual evidence. In addition, the lecturer should also emphasize the expected competence level the English Literature students should acquire.